Rentabilidad de La Empresa Comandato Sucursal Babahoyo por el Decrecimiento de sus Ventas - Zúñiga Sánchez, Ítalo Darío (2017)
The present study is made to the company COMANDATO, branch Babahoyo with reference to its profitability, and as for the decrease of its sales in the last periods, the management in the allocation of monthly budgets without previous studies, affecting the normal development and fulfillment of the goals for the Comandato store in Babahoyo to be a profitably favorable trade towards the fulfillment of the short-term objectives set by the executives. The characteristics that motivate the study of this dissertation is the high variation of non-attainment in the goals assigned monthly to the branch, affecting with this situation, the normal development of the same, incurring in the non payment of obligations to employees and suppliers. The decrease in revenues due to the decrease in sales has also prompted the company to not be able to fully comply with the cancellations of the income that would normally be received by in-store advisors, also causing demotivation and lack of commitment to obtaining the goals assigned to each one monthly.